Opportunities And Strategies For Traditional Halal Culinary In Modern Times - Janah, Roihatul; Asma; Adinugraha, Hendri Hermawan (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2022)
Traditional halal culinary is a culinary that needs to be developed because traditional halal culinary needs encouragement, because the culinary business is very promising. The purpose of this research is to find out how traditional halal culinary opportunities can survive and a good strategy so that traditional halal culinary can compete with today's modern culinary. It can be seen that the culinary business still has high resilience and is growing rapidly, especially food that is labeled and certified halal. Culinary is one of the characteristics of the identity of a region and most regions in Indonesia have it. The research method used in this study is a descriptive qualitative method, namely by conducting a library research method. The results of this study are to produce an understanding that traditional halal culinary has opportunities in developing its business today, and has several strategies that can develop traditional halal culinary businesses that can compete with modern culinary arts today. The strategy used is the 7P marketing mix strategy and digital strategy.